Comparative Analysis of the Situation of Interim Managers on the Basis of a Hungarian and a British Survey - György SZRETYKÓ (Revista de Management Comparat International)
The aim of this study, on the one hand, is to outline the types, competencies and functions of interim management, and on the other, to compare the situation of the Hungarian and British managers on the basis of empirical researches. Interim management appeared in Western Europe in the 1960s, while in the 1970s, as a result of oil-crises, the need for it increased. This was due to the fact that leaders of companies on the verge of bankruptcy accepted the suggestions of independent managers, who then temporarily took control over these companies. This is how interim management evolved. This kind of management differs from company consultants in that these managers not only developed a plan of survival but carried out the daily tasks of company management.